Constitutional, Administrative and Criminal Law Regulation of Protecting Rights of Internally Displaced Persons: Foreign Experience and Directions for Improvement - Olha Balynska; Maksym Korniienko; Oleh Martseliak; Vira Halunko; Ihor Mahnovskyi (UIN Sunan Gunung Djati, 2024)
The purpose of the article consists in revealing the constitutional, administrative and criminal law foundations of protecting rights of internally displaced persons, problems of implementing foreign experience and identification of directions for improvement. It is substantiated that the system of individual protection standards is a kind of international mechanism for ensuring first of all the status of rights and freedoms of internally displaced persons, the corresponding guarantees regulated by the norms of universal, regional and special treaties, implemented by authorized subjects of public administration in various spheres of society. Attention is focused on compliance with the Guidelines of 1998, which are the basis of the legal acts of the European Union, the Council of Europe and other democratic countries. However, the existing standards of individual protection are not uniform, and there is no corresponding institutional mechanism. Universal, supranational, regional, mandatory, recommendatory, permanent and temporary standards are singled out. The authors conclude that the Ukrainian authorities are entrusted with important tasks, functions and powers to guarantee the rights and freedoms of internally displaced persons, as well as tasks concerning implementation and protection of such rights and freedoms, restoration of violated rights and implementation of existing international standards and best foreign practices. Therefore, it is natural to improve Ukrainian legislation and ensure effective and accessible procedures. Proposed are ways to solve existing problems in the sphere of social protection, electoral law, housing and land rights, and provision of legal aid.